The investigation of autonomic functions in patients with psoriasis - Haligur, Beyzan Durul; Cicek, Demet; Bulut, Serpil; Berilgen, Muhammed Said (Wiley-Blackwell, 2012)
Background Psoriasis is a common Th1-mediated skin disease whose etiology remains obscure. Loss of sweating caused by retention hyperkeratosis is seen in psoriasis plaques, which is likely to have resulted from autonomic dysfunction. Objective In the present study, we aimed to evaluate autonomic nervous system (ANS) functions with regard to psoriasis and to examine whether there is an underlying ANS dysfunction. Materials and methods Fifty adult patients with plaque-type psoriasis and 20 healthy controls were enrolled in the present study. Results In this study, R-R interval variation (RRIV) was used to evaluate the parasympathetic system. No statistically significant difference was detected when RRIV values of the patient and the control groups were evaluated during normal and deep breathing (P > 0.05). It was determined that parasympathetic activity in the patient group remained unaffected. The sympathetic skin response (SSR) method was used for the evaluation of the sympathetic system. It was found that SSR latency and amplitude values of upper and lower extremities of the patient group were prolonged in comparison to those of the control group. The change in SSR latency of the upper extremity was found to be statistically significant (P < 0.05), whereas the changes in hand amplitude, foot latency, and foot amplitude values were not statistically significant (P > 0.05). It was determined that sympathetic activity in the patient group was affected. Conclusion In conclusion, we detected that a dysfunction was present in sympathetic nervous systems of patients with psoriasis. The parasympathetic nervous system functions were normal in patients with psoriasis.
Keywords: Sympathetic Skin-Response; Atopic-Dermatitis; Vitiligo; Keratinocytes; Diseases; Stress; System; Nerve; Index